Carregador de bateria de li-ion com sistema de equalização de carga - Gonschorowski, Ezequiel (2022)
This work aims to implement a lithium-ion battery charger with a passive equalization system. Lithium-ion batteries are too important for applications that demand storage systems, such as electric vehicles. Such applications demand a lot from batteries and their promising projections regarding their use. With this in mind, this work wants to implement a charger with charge equalization to improve the efficiency of this process. Therefore, the buck converter is proposed to implement the charger, since it is possible to control the output current and voltage, which are essential parameters for the charging algorithm. To make this charger, small signals from the buck converter are modeled, then an equivalent circuit of lithium-ion batteries is found. With this, the controller’s design and the equalization algorithm are carried out. All design stages are validated through simulations and comparisons with experimental results. Finally, the loading results are obtained experimentally and evaluated for their effectiveness.